2002
DOI: 10.1097/00004728-200207000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Lymph Nodes: Thin-Section CT Features of 19 Nodules

Abstract: Intrapulmonary lymph nodes are subpleural in the lower lung field. On thin-section CT, they are well circumscribed, homogeneous, round or ovoid, and smaller than 12 mm in maximal diameter. In the differential diagnosis of subpleural nodules located in the lower lung field, it should be kept in mind that they may be intrapulmonary lymph nodes even though the patient has malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…In our study, we identified, to our knowledge, two new independent negative predictive factors for malignancy in indeterminate solid NCNs detected in a population at high risk for lung cancer (21,22). The juxtavascular nodules may represent small lymph nodes or small branching vessels, while bronchiolitis or a small bronchiectasis may also appear as a vessel-or fissure-attached nodule.…”
Section: Discussionmentioning
confidence: 80%
“…In our study, we identified, to our knowledge, two new independent negative predictive factors for malignancy in indeterminate solid NCNs detected in a population at high risk for lung cancer (21,22). The juxtavascular nodules may represent small lymph nodes or small branching vessels, while bronchiolitis or a small bronchiectasis may also appear as a vessel-or fissure-attached nodule.…”
Section: Discussionmentioning
confidence: 80%
“…Nine subjects had died at the time of long-term follow-up. ( 24,25,27 ). In one study ( 27 ), 10 (53%) of 19 intrapulmonary lymph nodes were adjacent to the visceral pleura, with the remaining nine located 2-8 mm from the pleura.…”
Section: Discussionmentioning
confidence: 96%
“…Since there was no pathological material available from these benign nodules it can only be speculated what the underlying cause might be, including the spontaneous resolution of infectious lesions or local mucus impaction. Lymph nodes are less likely to be involved since the indeterminate nodules selected were situated within the lung parenchyma, while lymph nodes usually are located in the close vicinity of the broncho-vascular tree, the subpleural area or area attached to fissures [26,27].…”
Section: Discussionmentioning
confidence: 99%